2005
DOI: 10.1007/s10439-005-8758-0
|View full text |Cite
|
Sign up to set email alerts
|

Biofluid Mechanics of the Pulmonary System

Abstract: Presents an overview of leading areas of discovery in bio-fluid mechanics related to the pulmonary system, with particular reference to the airways. Areas briefly reviewed include airway gas dynamics, impedance studies, collapsible-tube studies, and airway liquid studies. Emphasis is placed on promising further directions, such as analysis of interacting fluid-mechanical or fluid-structure phenomena, multi-scale modeling across widely varying length and time scales, and integration of advanced simulations into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 105 publications
(85 reference statements)
0
17
0
Order By: Relevance
“…This gradient induces a convective Marangoni flow outward from the region of deposition. Induced Marangoni flow has potential use in improving drug delivery in patients with obstructive pulmonary conditions such as cystic fibrosis lung disease, where accumulation of dehydrated mucus alters airway aerodynamics and subsequent patterns of aerosol deposition in the lung (for examples, see references [57]).…”
Section: Introductionmentioning
confidence: 99%
“…This gradient induces a convective Marangoni flow outward from the region of deposition. Induced Marangoni flow has potential use in improving drug delivery in patients with obstructive pulmonary conditions such as cystic fibrosis lung disease, where accumulation of dehydrated mucus alters airway aerodynamics and subsequent patterns of aerosol deposition in the lung (for examples, see references [57]).…”
Section: Introductionmentioning
confidence: 99%
“…Biomedical examples of flow involving collapsible tubes are mainly in the circulatory and respiratory systems. Some examples include arteries [2], veins [3], urethras, vocal cords and pulmonary airways [4].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with advances in solid mechanics, ongoing investigations of biofluid mechanics in the pulmonary system (Bertram and Gaver 2005) are providing an improved understanding of lung injury mechanisms associated with closure and opening of fragile tissue structures (Kay et al 2004; Yalcin et al 2007), and generating multi-scale models for investigation of fluid dynamics in airways and lung vasculature (Tawhai and Burrowes 2008). At the interface of solid and fluid surfaces, recent experimental work has demonstrated that the airway-lining layer of mucus, which is optimized for lung defense and clearance, is responsive to airway shear stresses (Tarran et al 2005; Tarran et al 2006), and that pathological changes in mucus viscoelasticity can be targeted as a new therapeutic modality for patients with cystic fibrosis (Donaldson et al 2006; Tarran et al 2007).…”
Section: Micro-scale and Multi-scale Mechanicsmentioning
confidence: 99%